2018 Annual American Control Conference (ACC) 2018
DOI: 10.23919/acc.2018.8430756
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in Multi-Commodity Routing Networks: When does it help?

Abstract: We study the equilibrium behavior in a multicommodity selfish routing game with many types of uncertain users where each user over-or under-estimates their congestion costs by a multiplicative factor. Surprisingly, we find that uncertainties in different directions have qualitatively distinct impacts on equilibria. Namely, contrary to the usual notion that uncertainty increases inefficiencies, network congestion actually decreases when users over-estimate their costs. On the other hand, under-estimation of cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…For instance, there are a number of solutions for obtaining the optimal edge pricing [Cole et al 2003a,b;Fleischer et al 2004;Jelinek et al 2014]. Similarly, a number of works have examined how users' uncertainty level regarding edge costs or travel information (see, e.g., [Liu et al 2016;Sekar et al 2017;Thai et al 2016;Wu et al 2017]) impacts the price of anarchy. The price of anarchy under stochastic selfish routing game with risk-averse players has also been studied [Nikolova and Stier-Moses 2011].…”
Section: User Choice Versus Social Optimummentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, there are a number of solutions for obtaining the optimal edge pricing [Cole et al 2003a,b;Fleischer et al 2004;Jelinek et al 2014]. Similarly, a number of works have examined how users' uncertainty level regarding edge costs or travel information (see, e.g., [Liu et al 2016;Sekar et al 2017;Thai et al 2016;Wu et al 2017]) impacts the price of anarchy. The price of anarchy under stochastic selfish routing game with risk-averse players has also been studied [Nikolova and Stier-Moses 2011].…”
Section: User Choice Versus Social Optimummentioning
confidence: 99%
“…The price of anarchy under stochastic selfish routing game with risk-averse players has also been studied [Nikolova and Stier-Moses 2011]. It has been shown that, counter-intuitively, under some conditions on structure of edge-level congestion, equilibrium quality under uncertainty is better compared to the full information case [Sekar et al 2017]. The study of altruism is analogous to uncertainty in that it is a property associated with the user.…”
Section: User Choice Versus Social Optimummentioning
confidence: 99%
“…Player heterogeneity has been a topic of much interest, e.g., through player-specific resource cost functions [12] representing varied preferences [6] or uncertainties [3,18], while more complex models may consider driver's uncertainties over road conditions or demand [11]. There is evidence that providing incomplete information to drivers about road capacities may be worse than providing no information at all [2].…”
Section: Introductionmentioning
confidence: 99%